Analisis interpretasi matematis dalam mini riset mahasiswa melalui pembelajaran berbasis riset - Adi Slamet Kusumawardhana; Mayang Dintarini (University of Muhammadiyah Malang, 2021)
Statistics are studied in many fields of study including in Governmental Science, University of Muhammadiyah Malang (UMM). However, in reality, many UMM Government Science students do not understand the material and still have difficulty applying statistical methods, so it is necessary to provide mini research-based learning and analysis of interpretation abilities. The purpose of this research was to analyze students’ interpretative abilities in mini-research on research-based learning. The research used a qualitative descriptive method. The research sample consisted of 1 student who carried out mini research-based learning. The results of student’s reports were analyzed according to the indicators of interpretation ability. The result of the research indicated that the application of research-based learning in statistics subjects has a positive impact on students’ mathematical interpretation abilities can be seen from the achievement of the mathematical representation indicators found in the mini-research conducted by subject 1 in class. However, several things need to be improved in the mini-research conducted by subject 1, namely presenting problems and solving them in other forms. The descriptor wrote the notation in other forms and communicates the notation according to the idea.